A low‐cost, versatile data logging system for ecological applications. (11th March 2015) - Gandra, Miguel; Seabra, Rui; Lima, Fernando P.
Abstract: This work introduces a new lightweight, small, and modular data logger that can be used to record a vast array of environmental and physiological parameters in the field or in the laboratory, together with the corresponding software. The device, named NanoLogger, is based on the open‐source platform Arduino, featuring a custom‐made circuit board with easily serviceable connectors, a real‐time clock and a MicroSD memory card. The assemblage of the entire system does not require extensive electronics knowledge and can be done spending under 150 in parts, contrasting with most commercially available scientific loggers, which are at least one or two orders of magnitude more expensive. To demonstrate the system's capabilities and limitations, we connected the NanoLogger with (i) a triple‐axis accelerometer to log the effect of wave action on Fucus spiralis, (ii) a thermocouple to register the body temperature of intertidal gastropods ( Patella depressa and P. vulgata ) during a low tide, and (iii) an infrared sensor to record the heartbeat of a mussel ( Mytilus galloprovincialis ) in the laboratory. NanoLogger's relative low price and versatility can contribute to build networks of environmental loggers to monitor multiple environmental parameters across large geographical scales.